Developing a Learner-Centered Curriculum for a Rural Public Health Program - Njoku, Anuli; Wakeel, Fathima; Reger, Michael; Jadhav, Emmanuel; Rowan, Julie (International Journal of Teaching and Learning in Higher Education, 2017)
Rural communities, compared with their urban counterparts, have higher rates of disease and adverse health conditions, fueling disparities in health outcomes. This encourages the need for effective curricula to engage students and enable them to address such disparate health outcomes as imminent health professionals. Incorporating learner-centered teaching strategies, such as collaboration and power-sharing, into public health (PH) courses can enhance student learning and help faculty enable future health professionals to address needs of rural, underserved populations. Successfully engaging students to explore issues related to rural health disparities in their education, research, and training can thereby advance PH practice. This paper describes the collaborative efforts of five PH faculty, an instructional designer, and administrators to develop a learner-centered curriculum for a newly launched PH program in a rural Midwestern United States (US) university.
Keywords: Audience Response Systems; College Faculty; Course Descriptions; Disadvantaged; Diseases; Health Personnel; Instructional Design; Program Descriptions; Program Development; Public Health; Rural Areas; Student Centered Curriculum; Teacher Collaboration; Teaching Methods; Workshops; dept.pch

Peer Emotional Support, Perceived Self-Efficacy, and Mental Health Morbidities Among Student-Veterans at a Public University - Mastrocola, S.S.; Flynn, D.P. (Journal of Continuing Higher Education, 2017)
In the current U.S. military operational environment, it has been estimated that up to 700,000 troop years (cumulative years of service including multiple tours of duty) have been logged over the past decade since offensive campaigns began, following the September 11, 2001, terrorist attacks (Smith, Benight, & Cieslak, 2013). With this influx of eligible beneficiaries, the utilization of Veterans Administration (VA) education benefits more than doubled between 2001 and 2012 (U.S. Department of Veterans Affairs, 2013). This study examined the relationship between peer emotional support and perceived self-efficacy and their implications for, or relationship to, mental health morbidities in a postsecondary educational setting. The study included 39 matriculated student-veterans at an accredited postsecondary institution in New England. Participants answered 32 questions related to three constructs: perceived self-efficacy, peer emotional support, and mental health morbidity. It was found that a moderate, but significant, positive correlation exists between perceived self-efficacy and peer emotional support in student-veterans. A moderate but significant negative correlation was uncovered between perceived self-efficacy and mental health morbidity. In addition, this study found that first-year students report significantly lower peer emotional support than seniors and graduate students. It was also found that those veterans with only one deployment reported significantly greater self-efficacy than those who had deployed twice. This study serves as a conduit into future research on the multifaceted issues facing student-veterans. Copyright © 2017, Association for Continuing Higher Education.
Keywords: PTSD; VA; deployment; dept.pch; mental health; peer emotional support; perceived self-efficacy; veterans

Snacking, satiety, and weight: A randomized, controlled trial - Njike, Valentine Yanchou; Kavak, Yasemin; Treu, Judith A.; Doughty, Kimberly; Katz, David L. (American Journal of Health Promotion, 2017)
Purpose. To compare the effects of nut-based snack bars (NBSB) vs. prepackaged 200-kcal portions of typical conventional snack foods, when consumed over a 12-week period by a group of overweight adults. Design. Randomized, single-blind parallel design with two treatment groups. Setting. Clinical trial. Subjects. Thirty-four overweight participants were enrolled. Intervention. Commercially available NBSB or conventional snack foods as part of an ad libitum diet for 12 weeks. Measures. Primary outcome measures: body mass index, body weight, body composition, waist circumference. Secondary outcome measures: blood pressure, lipid profile, nutrients intake, hunger/satiety, quality of life. Analysis. Generalized linear models with time as repeated measure were used to analyze these data. Results. Daily consumption of NBSB for 12 weeks, as compared to daily consumption of conventional snacks, significantly reduced percentage body fat (-1.7% +/- 10.8% vs. 6.2% 6 9.3%; p = .04) and visceral fat (-1.3 +/- 5.9 vs. 2.7 +/- 4.0; p = .03). There were no between-group differences (p ¿ .05) for blood pressure, lipid panel, satiety, or quality of life measures. Conclusion. Our data suggest that daily consumption of NBSB for 12 weeks reduced body fat and had no adverse effects on weight, blood pressure, lipid profile, satiety, or quality of life in this small sample of overweight adults.
Keywords: Adult; Aged; Blood Pressure; Body Mass Index; Body Weight; Body Weights and Measures; Diet; Energy Intake; Female; Health focus: hunger/satiety, nutrition, quality of life; Humans; Male; Middle Aged; Nuts; Outcome measure: body mass index, body weight, body composition, waist circumference, blood pressure, lipid profile, nutrients intake, hunger/satiety, quality of life; Overweight; Quality of Life; Research purpose: intervention testing; Satiation; Setting: clinical; Single-Blind Method; Snacking, Satiety, Overweight, Prevention Research. Manuscript format: research; Snacks; Strategy: education, incentive; Study design: randomized, single-blind parallel trial; Target population age: overweight adults; Target population circumstances: geographic location; adult; aged; blood pressure; body mass; body weight; caloric intake; controlled study; dept.pch; diet; diet therapy; fast food; female; human; male; middle aged; morphometry; nut; obesity; peer-reviewed; quality of life; randomized controlled trial; satiety; single blind procedure

Lifestyle Medicine and the Management of Cardiovascular Disease. - Doughty, Kimberly N; Del Pilar, Nelson X; Audette, Amanda; Katz, David L (Current cardiology reports, 2017)
PURPOSE OF REVIEW: Evidence has clearly demonstrated the importance of lifestyle factors (e.g., diet, physical activity, smoking) in the development of cardiovascular disease (CVD). Interventions targeting these behaviors may improve outcomes for CVD patients. The aim of this review is to summarize the effects of lifestyle interventions in individuals with established CVD., RECENT FINDINGS: Most recent trials focused on diet, physical activity, stress reduction, or a combination of these. Findings were mixed, but most interventions improved at least some markers of cardiovascular risk. Few studies measured long-term clinical outcomes, but some suggested a possible benefit of stress reduction and multifaceted interventions on cardiovascular events. The benefits of lifestyle change for CVD patients have been established by decades of evidence. However, further research is needed to determine the optimal intensity, duration, and mode of delivery for interventions. Additional studies with long-term follow-up and measurement of clinical outcomes are also needed.
Keywords: *Cardiovascular Diseases; *Healthy Lifestyle; Cardiovascular Diseases; Cardiovascular Diseases/pc [Prevention & Control]; Cardiovascular Diseases/px [Psychology]; Diet; Disease Management; Exercise; Healthy Lifestyle; Humans; Life Style; Lifestyle; Mediterranean diet; Physical activity; Review; Stress reduction; aerobic exercise; cardiovascular disease; cardiovascular risk; dept.pch; disease management; evidence based medicine; follow up; healthy lifestyle; human; lifestyle; lifestyle modification; outcome assessment; physical activity; psychology; risk reduction; stress; therapy effect

Bridging the response to mass shootings and urban violence: exposure to violence in New Haven, Connecticut - Santilli, Alycia; Duffany, Kathleen O'Connor; Carroll-Scott, Amy; Thomas, Jordan; Greene, Ann; Arora, Anita; Agnoli, Alicia; Gan, Geliang; Ickovics, Jeannette (American Journal of Public Health, 2017)
We have described self-reported exposure to gun violence in an urban community of color to inform the movement toward a public health approach to gun violence prevention. The Community Alliance for Research and Engagement at Yale School of Public Health conducted community health needs assessments to document chronic disease prevalence and risk, including exposure to gun violence. We conducted surveys with residents in six low-income neighborhoods in New Haven, Connecticut, using a neighborhood-stratified, population-based sample (n=1189; weighted sample to represent the neighborhoods, n = 29 675). Exposure to violence is pervasive in these neighborhoods: 73% heard gunshots; many had family members or close friends hurt (29%)or killed (18%)by violent acts. Although all respondents live in low-income neighborhoods, exposure to violence differs by race/ ethnicity and social class. Residents of color experienced significantly more violence than did White residents, with a particularly disparate increase among young Black men aged 18 to 34 years. While not ignoring societal costs of horrific mass shootings, we must be clear that a public health approach to gun violence prevention means focusingonthedualepidemicofmass shootings and urban violence.
Keywords: Adolescent; Adult; African American; African Americans; Aged; Caucasian; Connecticut; European Continental Ancestry Group; Exposure to Violence; Female; Humans; Male; Mass Casualty Incidents; Middle Aged; Poverty Areas; Prevalence; Risk Factors; Self Report; Surveys and Questionnaires; Urban Population; Wounds, Gunshot; adolescent; adult; aged; dept.pch; ethnology; exposure to violence; female; gunshot injury; human; male; mass disaster; middle aged; poverty; prevalence; questionnaire; risk factor; self report; statistics and numerical data; urban population

Advancing school and community engagement now for disease prevention (ASCEND): A quasi-experimental trial of school-based interventions to prevent childhood obesity - Treu, Judith A.; Doughty, Kimberly; Reynolds, Jesse S.; Njike, Valentine Y.; Katz, David L. (American Journal of Health Promotion, 2017)
Purpose. To compare two intensity levels (standard vs. enhanced) of a nutrition and physical activity intervention vs. a control (usual programs) on nutrition knowledge, body mass index, fitness, academic performance, behavior, and medication use among elementary school students. Design. Quasi-experimental with three arms. Setting. Elementary schools, students' homes, and a supermarket. Subjects. A total of 1487 third-grade students. Intervention. The standard intervention (SI) provided daily physical activity in classrooms and a program on making healthful foods, using food labels. The enhanced intervention (EI) provided these plus additional components for students and their families. Measures. Body mass index (zBMI), food label literacy, physical fitness, academic performance, behavior, and medication use for asthma or attention-deficit hyperactivity disorder (ADHD). Analysis. Multivariable generalized linear model and logistic regression to assess change in outcome measures. Results. Both the SI and EI groups gained less weight than the control (p ¡ .001), but zBMI did not differ between groups (p = 1.00). There were no apparent effects on physical fitness or academic performance. Both intervention groups improved significantly but similarly in food label literacy (p = .36). Asthma medication use was reduced significantly in the SI group, and nonsignificantly (p - .10) in the EI group. Use of ADHD medication remained unchanged (p = .34). Conclusion. The standard intervention may improve food label literacy and reduce asthma medication use in elementary school children, but an enhanced version provides no further benefit.
Keywords: Anti-Asthmatic Agents; Asthma; Attention Deficit Disorder With Hyperactivity; Body Mass Index; Central Nervous System Stimulants; Child; Diet; Educational Status; Exercise; Female; Health Behavior; Health Knowledge, Attitudes, Practice; Health Promotion; Health focus: fitness/physical activity, nutrition; Humans; Male; Manuscript format: research; Obesity; Outcome measure: cognitive, behavioral, biometric; Physical Fitness; Prevention Research; Research purpose: intervention testing/program evaluation; School Health Services; Setting: family, school, local community; Socioeconomic Factors; Strategy: education, skill building/behavior change; Students; Study design: quasi-experimental; Target population age: youth; Target population circumstances: geographic location; antiasthmatic agent; attitude to health; body mass; central stimulant agent; child; clinical trial; dept.pch; diet; educational status; exercise; female; fitness; health behavior; health promotion; human; male; organization and management; peer-reviewed; school health service; socioeconomics

Associations between prediagnostic blood glucose levels, diabetes, and glioma. - Schwartzbaum, Judith; Edlinger, Michael; Zigmont, Victoria; Stattin, Par; Rempala, Grzegorz A; Nagel, Gabriele; Hammar, Niklas; Ulmer, Hanno; Foger, Bernhard; Walldius, Goran; Manjer, Jonas; Malmstrom, Hakan; et al. (Scientific Reports, 2017)
Previous literature indicates that pre-diagnostic diabetes and blood glucose levels are inversely related to glioma risk. To replicate these findings and determine whether they could be attributed to excess glucose consumption by the preclinical tumour, we used data from the Apolipoprotein MOrtality RISk (AMORIS) (n = 528,580) and the Metabolic syndrome and Cancer project (Me-Can) cohorts (n = 269,365). We identified individuals who were followed for a maximum of 15 years after their first blood glucose test until glioma diagnosis, death, emigration or the end of follow-up. Hazard ratios (HRs), 95% confidence intervals (CIs) and their interactions with time were estimated using Cox time-dependent regression. As expected, pre-diagnostic blood glucose levels were inversely related to glioma risk (AMORIS, P trend = 0.002; Me-Can, P trend = 0.04) and pre-diagnostic diabetes (AMORIS, HR = 0.30, 95% CI 0.17 to 0.53). During the year before diagnosis, blood glucose was inversely associated with glioma in the AMORIS (HR = 0.78, 95% CI 0.66 to 0.93) but not the Me-Can cohort (HR = 0.99, 95% CI 0.63 to 1.56). This AMORIS result is consistent with our hypothesis that excess glucose consumption by the preclinical tumour accounts for the inverse association between blood glucose and glioma. We discuss additional hypothetical mechanisms that may explain our paradoxical findings.
Keywords: *Blood Glucose/me [Metabolism]; *Brain Neoplasms/di [Diagnosis]; *Diabetes Mellitus, Type 2/di [Diagnosis]; *Glioma/di [Diagnosis]; *Prediabetic State/di [Diagnosis]; Adult; Aged; Biomarkers; Biomarkers/bl [Blood]; Blood Glucose; Brain Neoplasms; Brain Neoplasms/bl [Blood]; Brain Neoplasms/mo [Mortality]; Brain Neoplasms/pa [Pathology]; Diabetes Mellitus, Type 2; Diabetes Mellitus, Type 2/bl [Blood]; Diabetes Mellitus, Type 2/mo [Mortality]; Diabetes Mellitus, Type 2/pa [Pathology]; Female; Glioma; Glioma/bl [Blood]; Glioma/mo [Mortality]; Glioma/pa [Pathology]; Humans; Longitudinal Studies; Male; Middle Aged; Prediabetic State; Prediabetic State/bl [Blood]; Prediabetic State/mo [Mortality]; Prediabetic State/pa [Pathology]; Prognosis; Proportional Hazards Models; Risk Factors; Time Factors; adult; aged; biological marker; blood; brain tumor; dept.pch; female; glioma; glucose blood level; human; impaired glucose tolerance; longitudinal study; male; metabolism; middle aged; mortality; non insulin dependent diabetes mellitus; pathology; peer-reviewed; prognosis; proportional hazards model; risk factor; time factor

Predictors of success for community-driven water quality management—Lessons from three catchments in New Zealand - Tyson, Ben; Unson, Christine; Edgar, Nick (Applied Environmental Education & Communication, 2017)
Three community engagement projects on the South Island of New Zealand are enacting education and communication initiatives to improve the uptake of best management practices on farms regarding nutrient management for improving water quality. Understanding the enablers and barriers to effective community-based catchment management is fundamental to planning, implementing and evaluating these initiatives. This article investigates some key predictors of success or determinants of effective community engagement. Six factors were identified: access to science, training, and information; confidence in regulatory policies; leadership; farm planning and monitoring; trust in the public; and concern for water quality. © 2017 Taylor & Francis Group, LLC.
Keywords: dept.pch

Getting men to explore safer sex responsibility: the use of Photovoice in health promotion research - Breny, Jean M.; Lombardi, Deirdre; Madden, Devin; Smoyer, Amy B. (SAGE Research Methods Cases: Health, 2017)
Keywords: dept.pch; dept.swk

Prevalence of malaria infection and ABO human blood group in Dar-es-Salaam, Tanzania - Nwangwu, John; Roland, Ivan; Mbelwa, David; Magori, Cassian; Evans, Marian; Price, Cynthia (Advances in Infectious Diseases, 2017)
Keywords: dept.pch